Manejo del sistema de inventario y su incidencia en los estados financieros del sector ferretero en la parroquia Izamba de la ciudad de Ambato. - Manobanda Guamán, Cristian Bladimir (2019)
This research aims to analyze and evaluate the impact of inventory system management, and its effect on the financial statements of the hardware stores "THE CONSTRUCTOR" and "INDOAMERICA FRANCHISEE DISENSA." These hardware companies need to have an inventory control system to facilitate the handling of the merchandise allowing to optimize economic resources reducing the time in the decision making to generate an increase sales, therefore reflecting higher profits. Consequently, the inventory management at the companies is the basis for getting better control of the activities carried out; the research has the following objectives: to detail the current situation of the two companies in the Izamba hardware sector, and to carry out an internal and external situational analysis to determine strengths, weaknesses, opportunities, and threats, that will help determine the problem, which will be analyzed through the SWOT tool. The research was based on a qualitative and documentary approach through the collection of information which is carried out by primary and secondary sources, the interview technique aimed at the owners of the companies "El Constructor and Indoamerica" was used; the survey was also carried out through a questionnaire addressed to their eight employees as well. After that, inventory systems were analyzed for a better interpretation. Finally, financial statements such as balance sheets, profit and loss statements of the companies investigated were compared. The project was also supported with mathematical calculations through financial ratios with the main accounts to demonstrate that the management of the inventory system affects the financial statements.